The main stages of formation and development of the literary karachay-balkarian language (to the 100th anniversary of formation of the Kabardino-Balkarian Republic) - Makhti Z. Ulakov; Boris A. Musukov (Кавказология, 2022)
The article is devoted to the study of the formation and development of the literary Karachay-Balkar language history over the past hundred years. An overview of its study is given, current problems of functioning are outlined, and prospects for further improvement are determined. A multi-aspect analysis of the studied language is conducted, considering the main, crucial publications for the period under review. The fundamental projects “Explanatory dictionary of the Karachay-Balkarian language” and “Modern Karachay-Balkarian language” stand out as special achievements of Karachay-Balkarian linguistics. A new periodization of the development of the literary Karachay-Balkar language and its evolution into the status of the state language is proposed. Attention is drawn to the tasks considered for philologists to determine, at the junction of humanitarian disciplines, the specific contribution of the classics of the Balkar and Karachay literatures to strengthen the norms of the language being studied. Attention is paid to the development of issues related to writing, alphabet, spelling and terminology. For the further successful functioning of the native language, it is necessary to improve the very practice of creating complex studies, its method, and the unification of lexical norms. The expediency of developing scientific principles for the selection of linguistic phenomena is indicated, considering regional characteristics. The perspective possibilities of expansion of functions provided by the official status of “literary language” in two constituent entities of the Russian Federation are substantiated: the Kabardino-Balkarian and Karachay-Cherkess republics.